Vitamin C Inhibits Blood-Stage Plasmodium Parasites via Oxidative Stress - Shi, Xiaoyu; Wei, Meng; Xu, Zihao; Liu, Ying; Zhang, Mujia; Lv, Li; Wang, Qian (Frontiers in Cell and Developmental Biology, 2021)
During the Plasmodium erythrocytic cycle, glucose is taken up by glucose transporters (GLUTs) in red blood cells (RBCs) and supplied to parasites via the Plasmodium hexose transporter (HT). Here, we demonstrate that the glucose uptake pathway in infected RBCs (iRBCs) can be hijacked by vitamin C (Vc). GLUTs preferentially transport the oxidized form of Vc, which is subsequently reduced in the cytosol. Vc, which is expected to burden the intracellular reducing capacity, inhibits Plasmodium berghei (P. berghei) and Plasmodium falciparum (P. falciparum) growth. Vc uptake is drastically increased in iRBCs, with a large proportion entering parasites. Increased absorption of Vc causes accumulation of reactive oxygen species, reduced ATP production, and elevated eryptosis in iRBCs and apoptosis in parasites. The level of oxidative stress induced by Vc is significantly higher in iRBCs than uninfected RBCs, not seen in chloroquine or artemesinin-treated iRBCs, and effective in inhibiting chloroquine or artemisinin-resistant parasites. These findings provide important insights into the drug sensitivity of Plasmodium.